Visual Outcome of Phacoemulsification at Griya Husada Eye Center, Madiun, Indonesia - Astrid Feriza; Nurwasis Nurwasis; Sukoto Sukoto (Vision Science and Eye Health Journal, 2022)
Introduction: Sight is one of the most important senses that absorbs more than 80% of visual information. However, visual disturbances are common, ranging from mild to severe disturbances that can lead to blindness. A cataract is the leading cause of blindness in Indonesia; it is accountable for 77.7% of all blindness. Phacoemulsification is a new ECCE technique in which cloudy or cataractous lenses are removed through a 2-3 mm incision with no sutures. The advantages of this small incision are faster visual recovery, minimal astigmatic induction due to surgery, and minimal postoperative complications and inflammation. Purpose: This study aimed to measure visual outcomes in senile cataract patients after phacoemulsification surgery at Griya Husada Eye Center, Madiun, Indonesia. Methods: A Retrospective study was carried out among senile cataract patients who had phacoemulsification surgery at Griya Husada Eye Center, Madiun, Indonesia between January and May 2021. The best corrected visual acuity (BCVA) was recorded on the fourteenth day. Results: From 292 patients, postoperative visual acuity in the good category (6/6 - 6/18) was 94.9%, in the moderate category (<6/18 - 6/60) was 1.7%, and in the poor category (<6/60) was 3.4%. Conclusions: Postoperative visual acuity with phacoemulsification at Griya Husada Eye Center, Madiun, Indonesia showed satisfactory results and met World Health Organization’s (WHO) standards.